2011
DOI: 10.1111/j.1365-2230.2010.03871.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin levels in psoriasis and correlation with cutaneous disease activity

Abstract: These results indicate that serum PRL levels may serve as a biological marker of psoriatic disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…22,31,32 ). More recent publications have demonstrated the positive correlation between PASI score and serum PRL levels in 20 and 23 patients with PV treated with tacalcitol 21 and propylthiouracil 33 , respectively, and the serum PRL levels were increased in both studies in PV patients compared to healthy individuals. However, two recent studies with 30 PV patients did not detect hyperprolactinemia or elevated PRL levels compared to healthy controls 34,35 and although PRL levels decreased after treatment of newly diagnosed PV, no correlation with PASI was found 35 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…22,31,32 ). More recent publications have demonstrated the positive correlation between PASI score and serum PRL levels in 20 and 23 patients with PV treated with tacalcitol 21 and propylthiouracil 33 , respectively, and the serum PRL levels were increased in both studies in PV patients compared to healthy individuals. However, two recent studies with 30 PV patients did not detect hyperprolactinemia or elevated PRL levels compared to healthy controls 34,35 and although PRL levels decreased after treatment of newly diagnosed PV, no correlation with PASI was found 35 .…”
Section: Discussionmentioning
confidence: 74%
“…30% of patients were treated by biologics. This is in contrast to Dilmé-Carreras 21 and Malligarjunan 33 as in these studies, systemic and topical treatment was unwarranted before enrollment. While PRL release can be influenced by chronic emotional stress 36 and PV is recognised as a disease with a psychological component, the small differences in treatment might have an impact on the perception of the disease and levels of psychological stress.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, these findings correspond well to an earlier study that had shown a positive association between raised serum PRL levels and psoriasis. An intriguing new dimension in the Dilme-Carreras et al [3] study was the finding that clinical improvement in psoriasis, in response to treatment with topical tacalcitol, was accompanied by a decrease in serum PRL level, and that there was a correlation between serum PRL level and clinical severity as assessed by PASI score. Comparing the results of this study with the results of the present study have showed increased serum prolactin level in the studied group of patients with plaque-type psoriasis vulgaris and decrease of this level after 3 months period of treatment with NB-UVB.…”
Section: Discussionmentioning
confidence: 99%
“…Dilme-Carreras et al [3] carried out a study on 20 patients with plaque-type psoriasis before and after a 6-weeks period of topical treatment. Results were compared with a group of 20 healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%